Co3O4−CeO2 Nanocomposites for Low‐Temperature CO Oxidation. Issue 68 (10th June 2021) - Yang, Jingxia; Yigit, Nevzat; Möller, Jury; Rupprechter, Günther
Abstract: In an effort to combine the favorable catalytic properties of Co3 O4 and CeO2, nanocomposites with different phase distribution and Co3 O4 loading were prepared and employed for CO oxidation. Synthesizing Co3 O4 ‐modified CeO2 via three different sol‐gel based routes, each with 10.4 wt % Co3 O4 loading, yielded three different nanocomposite morphologies: CeO2 ‐supported Co3 O4 layers, intermixed oxides, and homogeneously dispersed Co. The reactivity of the resulting surface oxygen species towards CO were examined by temperature programmed reduction (CO‐TPR) and flow reactor kinetic tests. The first morphology exhibited the best performance due to its active Co3 O4 surface layer, reducing the light‐off temperature of CeO2 by about 200 °C. In contrast, intermixed oxides and Co‐doped CeO2 suffered from lower dispersion and organic residues, respectively. The performance of Co3 O4 ‐CeO2 nanocomposites was optimized by varying the Co3 O4 loading, characterized by X‐ray diffraction (XRD) and N2 sorption (BET). The 16–65 wt % Co3 O4 −CeO2 catalysts approached the conversion of 1 wt % Pt/CeO2, rendering them interesting candidates for low‐temperature CO oxidation. Abstract : Co3 O4 −CeO2 nanocomposites with three different morphologies, that is, CeO2 ‐supported Co3 O4 layers, intermixed oxides, and homogeneously dispersed Co, were used for CO oxidation. Both CO‐TPR and CO oxidation kinetics indicated that the layered structure exhibited the best performance for the same Co3 O4 loading of 10.4 wt %. The CO oxidation activity increased for higher Co3 O4 amount, approaching activity comparable to Pt/CeO2 .